Avaliaç\~ao do impacto econômico setorial da banda larga - Alexandre Ywata de Carvalho; Mário Jorge Cardoso de Mendonça; Marcus Gerardus Lavagnole; Luis Alberto Toscano Medrano (Instituto de Pesquisa Econômica Aplicada (IPEA), 2018)
– Although there is agreement that the effect of broadband expansion on the economy, from an general overview, is positive; not an unanimous voice arguments that this impact be positive on all sectors. By applying a multivariate two way panel data model and estimated by bayesian methodology, this study aims to determine the effect of broadband expansion on the sectors of the economy. In order to take into account the geographical, social and economic differences among municipalities cluster analysis was employed in order to isolate groups of municipalities with approximate characteristics. The results illustrate that the impact of broadband is not positive for all sectors, being positive in the most dynamic and technology-intensive sectors such as the industrial and service sectors; and negative where this does not happen as in agricultural sector.
Keywords: O57; O47; L69; 330; broadband; multivariate model; panel data; clustering; Gibbs sampler